PUTRAFLEX: UPM flexible curriculum - Abdul Rani, Mohd Zariat; Saad, Wan Zuhainis; Rokhani, Fakhrul Zaman; Wan Jaafar, Wan Marzuki; Ibrahim, Nor Azowa; Mokhtar, Makhfudzah; Zakaria @ Ya, Muta Harah; Man, Nor Azirawani (Centre for Academic Development (CADe), Universiti Putra Malaysia, 2019)
PUTRAFLEX is structured with an underpinning philosophy of producing Future-Proof PUTRA Graduates through a curriculum that is ﬂexible in nature, promotes the convergence of disciplines, and oﬀers diverse study paths. Accordingly, PUTRAFLEX contains the concepts and guidelines for its implementation at UPM.